2017
DOI: 10.1590/1519-6984.170155
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive dynamics of Lycengraulis grossidens (Clupeiformes: Engraulidae) and Platanichthys platana (Clupeiformes: Clupeidae) in a subtropical coastal lagoon

Abstract: We evaluated the reproductive dynamics of two fish species, Lycengraulis grossidens and Platanichthys platana, in a subtropical freshwater coastal lagoon (Peri Lagoon) in Brazil. Samples were collected from nine sites every two months from June 2008 to April 2012. Different fishing methods were used to capture larvae, juveniles, and adults. Limnological variables were obtained using multiparameter probe. More females than males were collected of both fish species and the chi-square test (χ 2 ) was used to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…This scenario can help explain why only two maturation phases were observed in all females collected during the sampling period, hypothesizing that A. bimaculatus females are always prepared for reproduction, depending only on an environmental trigger. This behaviour has already been observed in other species such as the sardines Lycenaraulis grossiden and Platanichthys platana (Lopes et al, 2018), which demonstrated the ability to adjust their reproduction based in environmental conditions and to reproduce in any season of the year. Nevertheless, reproduction was mainly triggered by temperature for those species, differing from the present findings.…”
supporting
confidence: 66%
“…This scenario can help explain why only two maturation phases were observed in all females collected during the sampling period, hypothesizing that A. bimaculatus females are always prepared for reproduction, depending only on an environmental trigger. This behaviour has already been observed in other species such as the sardines Lycenaraulis grossiden and Platanichthys platana (Lopes et al, 2018), which demonstrated the ability to adjust their reproduction based in environmental conditions and to reproduce in any season of the year. Nevertheless, reproduction was mainly triggered by temperature for those species, differing from the present findings.…”
supporting
confidence: 66%
“…Most Clupeiformes (Clupeidae and Engraulidae) exhibit extended spawning periods throughout the year (Lopes et al, 2018;Trindade-Santos & Freire, 2015). They lay pelagic eggs and have short planktonic life cycles (Able & Fahay, 1998;Araújo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Limited environmental studies have been conducted on this lagoon since the 1970s, resulting in significant gaps in our understanding of its functions (Teive et al, 2008). Regarding the ichthyofauna, only a few studies have focused on adult animals, and even fewer have investigated the distribution of fish eggs and larvae in this lagoon (Ferreira et al, 2017;Lopes et al, 2018).…”
Section: Graphical Abstractmentioning
confidence: 99%
“…A reprodução, geralmente, ocorre sazonalmente entre os momentos de seca e enchente dos corpos d'água (ZACARDI et al, 2017b;PONTE et al, 2019). Além de ser influenciada pela variação espacial e temporal dos fatores ambientais como a temperatura da água, volume de precipitação, pH e condutividade elétrica (ZACARDI et al, 2017a;CAJADO et al, 2020), maximizando a sobrevivência da prole e garantindo a manutenção da população local (LOPES et al, 2018).…”
Section: Introductionunclassified